2017
DOI: 10.1111/etap.12233
|View full text |Cite
|
Sign up to set email alerts
|

Fail but Try Again? The Effects of Age, Gender, and Multiple–Owner Experience on Failed Entrepreneurs’ Reentry

Abstract: We investigate what leads failed entrepreneurs to reenter entrepreneurship by taking a developmental career perspective. Specifically, we hypothesize that the age of failed entrepreneurs has a non-linear relationship with the likelihood of reentering entrepreneurship that follows different career stages (early, middle, and late). The gender of failed entrepreneurs and multipleowner experience in the failed firm are hypothesized to be moderators of this relationship. We test our hypotheses using a database cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 169 publications
(299 reference statements)
4
63
0
7
Order By: Relevance
“…Most previous studies on gender and entrepreneurship indicate that males display higher self-efficacy and higher risk-taking behavior than females, but show less need for entrepreneurial education (Ba u, Sieger, Eddleston, & Chirico, 2017;Eddleston, Ladge, Mitteness, & Balachandra, 2016;Wilson et al, 2007). Males with an entrepreneurial family background are more likely to start their own business than females with an entrepreneurial family background (Matthews & Moser, 1996).…”
Section: Entrepreneurship In the Western Countriesmentioning
confidence: 99%
“…Most previous studies on gender and entrepreneurship indicate that males display higher self-efficacy and higher risk-taking behavior than females, but show less need for entrepreneurial education (Ba u, Sieger, Eddleston, & Chirico, 2017;Eddleston, Ladge, Mitteness, & Balachandra, 2016;Wilson et al, 2007). Males with an entrepreneurial family background are more likely to start their own business than females with an entrepreneurial family background (Matthews & Moser, 1996).…”
Section: Entrepreneurship In the Western Countriesmentioning
confidence: 99%
“…These are official statistics, which are considered highly accurate and reliable (cf. Baù et al 2017;Wennberg et al 2011;Wiklund et al 2013).…”
Section: Samplementioning
confidence: 99%
“…Research has shown that education is an important factor in explaining a person's decision to start a business, especially for women in high-income countries (Allen et al 2007). Similarly, it has been shown that prior experiences as an entrepreneur might provide important skills and social capital that could be exploited in a novel initiative (Baù et al 2017); thus, we controlled for mother's prior entrepreneurial experience, dummy coded as "1" if the mother had an entrepreneurial activity terminated or sold before the birth of the child, "0" otherwise. Moreover, to provide the complementary perspective of the partner's parental leave used as an independent variable, we control for the mother's parental leave, calculated as the mother's parental benefits paid in the year, divided by the mother's individual's income in the same year.…”
Section: Control Variablesmentioning
confidence: 99%
“…The literature on organizational learning and entrepreneurial learning argues that new ventures are able to evaluate the appropriateness of various change initiatives and that, as a consequence, post-founding, entrepreneurs adapt based on the feedback they receive (Minniti & Bygrave, 2001). This literature claims not only that entrepreneurs learn from previous experiences (Baù et al, 2017), but also that new ventures learn differently and more effectively than established organizations (e.g., Sapienza et al, 2006;Zahra et al, 2000).…”
Section: Adaptation Mechanisms and Short-term Revenue Volatilitymentioning
confidence: 99%
“…Founder age is expected to have a broadly positive relationship with new venture survival (Baù et al, 2017) being lowest amongst the young and inexperienced (Parker 2018), hence we control for founder age (Founder age) and founder age squared (Founder age_sq).…”
Section: Control Variablesmentioning
confidence: 99%